Research on Virtualization of Mobile Core Network Architecture - Wei Xiong; Bingyi Fang; Yunyong Zhang; Jun Wu; Sufen Li (Dianxin kexue)
The NFV and SDN were introduced, the current work in network virtualization was analyzed and its requirements were concluded. Aimed at network architecture of mobile core network, and then the architecture of core network virtualization were proposed and brief introduction was made which was very import to guide the evolution of core network.